Synthesizing the Influences of Green Supply Chain Management towards Organisational Outcomes - Bambang Tri Cahyono; Avinash Pawar; Koes Indrati; Henry Loupias (International Journal of Supply Chain Management, 2020)
Today sustainability is the biggest concern for the entire world, and it is one of the foremost objectives of the United Nations sustainability goals. In the context of businesses, supply chain management (SCM) is the most critical function which decides the company’s performance. However, it is necessary to understand the influence of green supply chain management (GSCM) on organizations. This paper reviews the literature to explore the crucial dimensions of GSCM and analyses its influence on organizational outcomes. In order to apprehend the in-depth details, the authors have adopted a mixed research methodology to collect qualitative and quantitative data. The data from 74 companies were composed using the survey questionnaire and interview method using stratified sampling. The analysis is accomplished to recognize the influences of GSCM on organizational outcomes through the components of green supply chain drivers, green supply chain support activities, green supply chain practices, and organizational supply chain strategies. The findings and conclusion of the study highlight the relationship and positive influence of GSCM on the organizational outcomes in the form of financial and environmental performance.